2017
DOI: 10.4103/1735-3327.201138
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of salivary creatinine, urea, and potassium levels to assess dialysis need in renal failure patients

Abstract: Background:The prevalence of chronic renal failure is increasing because of increase in chronic debilitating diseases and progressing age of population. These patients experience accumulation of metabolic byproducts and electrolyte imbalance, which has harmful effects on their health. Timely hemodialysis at regular intervals is a life-saving procedure for these patients. Salivary diagnostics is increasingly used as an alternative to the traditional methods. Thus, the aim of the present study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 17 publications
6
30
0
1
Order By: Relevance
“…Regardless of the mechanism(s) accounting for the abundance of phosphorus in saliva, the evidence of a correlation between saliva phosphorus and plasma phosphorus could be explained hypothesizing that plasma phosphorus controls the secretion and/or the diffusion of phosphorus in saliva. With regard to urea, its saliva concentrations were almost identical and highly correlated with plasma urea in accordance with previous observations . The high‐order correlation of saliva urea with plasma urea and the identity of urea concentrations in plasma and saliva reasonably reflected the chemical characteristics of urea, that is, extremely soluble and diffusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the mechanism(s) accounting for the abundance of phosphorus in saliva, the evidence of a correlation between saliva phosphorus and plasma phosphorus could be explained hypothesizing that plasma phosphorus controls the secretion and/or the diffusion of phosphorus in saliva. With regard to urea, its saliva concentrations were almost identical and highly correlated with plasma urea in accordance with previous observations . The high‐order correlation of saliva urea with plasma urea and the identity of urea concentrations in plasma and saliva reasonably reflected the chemical characteristics of urea, that is, extremely soluble and diffusive.…”
Section: Discussionmentioning
confidence: 99%
“…The use of saliva for laboratory tests has been investigated in various medical areas because saliva could be used as a noninvasive diagnostic tool . An important prerequisite for the use of saliva in diagnostic workup is that the salivary levels of the marker associated with a given disorder should mirror the profile of the marker in biological samples used as gold standard in medical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its value depends on muscular mass and thus it depends on tubular secretion sex and age. It has been demonstrated that cystatin C level increases even with creatinine clearance decrease below 1.57 ml.s -1 when the creatinine level has not yet changed [11].…”
Section: /mentioning
confidence: 99%
“…In mammalians, about one-quarter of circulating inorganic nitrate (NO3−) derived from the diet. The salivary glands are the main responsible for delivering NO3-in saliva (5). Changes in salivary composition were demonstrated in CKD subjects.…”
Section: Introductionmentioning
confidence: 99%